2019
DOI: 10.1136/jclinpath-2019-206189
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of associations between 10 common gene polymorphisms and gastric cancer: evidence from a meta-analysis

Abstract: AimsAssociations between polymorphisms in cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4)/mannose-binding lectin (MBL)/interleukin-4 (IL-4)/interleukin-6 (IL-6)/phospholipase C ε−1 (PLCE1) and gastric cancer (GC) were already reported by many studies, yet the conclusions of these studies were somehow controversial. The aim of this meta-analysis was to better clarify associations between polymorphisms in CTLA-4/MBL/IL-4/IL-6/PLCE1 and GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The latter, in turn, triggers an alternative complement activation pathway to recognize tumor cells. Of note, disease development is dependent on the MBL gene polymorphism, which likely affects the genetic predisposition to this type of cancer, although this was not confirmed by the meta-analysis 13 .…”
Section: The Role Of Mannose In Gastric Cancer Progressionmentioning
confidence: 85%
See 1 more Smart Citation
“…The latter, in turn, triggers an alternative complement activation pathway to recognize tumor cells. Of note, disease development is dependent on the MBL gene polymorphism, which likely affects the genetic predisposition to this type of cancer, although this was not confirmed by the meta-analysis 13 .…”
Section: The Role Of Mannose In Gastric Cancer Progressionmentioning
confidence: 85%
“…At the same time, Wang et al 12 did not detect a significant difference among the entire cohort of patients and donors in a study involving the MBL2 gene polymorphism in 388 patients with GC and 144 healthy donors in the Japanese population. Moreover, Xie et al 13 reported no association between the MBL gene polymorphism and GC in a meta-analysis of 43 published studies.…”
Section: The Role Of Mannose In Gastric Cancer Progressionmentioning
confidence: 99%
“…We confirmed the significance of the two SNPs previously reported, rs3765524 and rs2274223, and revealed another SNP in PLCE1 , rs3781264, through genotyping and logistic regression in this case-control study was associated with the GC risk. Abnet et al (2010) firstly used GWAS to identify those variants of PLCE1 had a significant correlation with GC in the Chinese Han population Until now, an increasing number of studies have identified a shared susceptibility locus in PLCE1 such as rs2274223 A > G and rs3765524 C > T for gastrointestinal cancer ( Abnet et al, 2010 ; Umar et al, 2013 ; Cui et al, 2014b ; Liu et al, 2014 ; Malik et al, 2014 ; Mocellin et al, 2015 ; He et al, 2016 ; Gu et al, 2018 ; Li et al, 2018 ; Liang et al, 2019 ; Xie et al, 2020 ), and the most reported SNP of PLCE1 was the former, but the conclusions lack consistency. A meta-analysis showed that PLCE1 rs2274223 polymorphism resulted in susceptibility to esophageal and GC in Asians ( Umar et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…В то же время Z. Xie и соавт. [28] в своем метаанализе, включавшем 43 опубликованных исследо-вания, не обнаружили ассоциации между полиморфизмом гена MBL и РЖ.…”
Section: обзор литературы и клинико-экспериментальное исследование | ...unclassified
“…com / ), что может отражаться на его функциональной активности [7]. Одно из первых исследований уровня экспрессии маннозосвязывающего лектина при РЖ показало зависимость развития заболевания от полиморфизма гена MBL, что, вероятно, сказывается на генетической предрасположенности к этому виду онкологии, хотя это и не подтвердилось по результатам метаанализа [28]. Выраженная экспрессия MR в опухолях желудка являлась фактором неблагоприятного прогноза в китайском исследовании [28].…”
Section: обзор литературы и клинико-экспериментальное исследование | ...unclassified